2006
DOI: 10.1183/09031936.06.00072105
|View full text |Cite
|
Sign up to set email alerts
|

Stable COPD: predicting benefit from high-dose inhaled corticosteroid treatment

Abstract: The role of inhaled corticosteroids in the management of chronic obstructive pulmonary disease (COPD) remains controversial. The purpose of this study was to evaluate whether sputum eosinophilia (defined as eosinophils o3%) predicts clinical benefit from inhaled corticosteroid treatment in patients with smoking-related clinically stable moderate-to-severe COPD.Forty consecutive patients with effort dyspnoea (mean age 67 yrs; 52 pack-yr smoking history; post-bronchodilator forced expiratory volume in one second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
186
3
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(210 citation statements)
references
References 36 publications
10
186
3
11
Order By: Relevance
“…The present results indicate a preferential distribution of eosinophils towards the lumen. This may have implications for current and future treatment strategies [41][42][43][44] in chronic obstructive pulmonary disease patients with clinical symptoms of chronic bronchitis. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results indicate a preferential distribution of eosinophils towards the lumen. This may have implications for current and future treatment strategies [41][42][43][44] in chronic obstructive pulmonary disease patients with clinical symptoms of chronic bronchitis. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that treatment with steroids may reduce numbers of sputum eosinophils in patients with COPD [40,41], whereas sputum eosinophilia in COPD may be predictive of a clinical response to steroid treatment [42,43]. Distinct inflammatory cell profiles may require different (antiinflammatory) interventions.…”
Section: Discussionmentioning
confidence: 99%
“…COPD with concomitant asthma has been associated with more eosinophilic inflammation, as shown by more peripheral and sputum eosinophils [Kitaguchi et al 2012;Papi et al 2000], and in addition, these patients responded better to ICS [Brightling et al 2005;Kerstjens et al 1993;Kitaguchi et al 2012;Leigh et al 2006]. Iwamoto showed increased sputum eosinophilia in patients with asthma and ACOS compared with healthy smokers and those with COPD [Iwamoto et al 2014].…”
Section: Airway Inflammationmentioning
confidence: 99%
“…Taken together, these findings suggest that the airway structural changes can impair respiratory function and aggravate asthmatic symptoms even in patients with mild asthma. Although inhalation of steroids can inhibit airway inflammation in asthma, it is still unclear whether it can reverse airway structural changes [30] . Our research found that inhalation of budesonide-ormoterol for one year could effectively alleviate asthma symptoms, improve lung function, reduce airway hyper-responsiveness, inhibit inflammatory cell infiltration, and reverse airway remodeling in patients with asthma.…”
Section: Discussionmentioning
confidence: 99%